2022
DOI: 10.1007/s40430-022-03560-5
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing micromachining errors in EDM of Inconel 600 using various biodegradable dielectrics

Abstract: Inconel 600 is a Ni-based superalloy having exclusive properties like high strength and stability in harsh conditions. However, its accurate machining is challenging via conventional cutting methodologies. As a result, the use of electric discharge machining is common in cutting Inconel 600 precisely. But the intrinsic issue of overcut associated with traditional EDM limits its appreciation in cutting Ni-based alloy. Moreover, conventional dielectric oil used in EDM releases hazardous fumes and gases that put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The reason is that Olive oil has the lower value of dielectric strength (26-41 kV) among the other dielectrics used in this study, and thereof, the ionization of the said biodegradable oil becomes easier. This ionization phenomenon generates high discharge heat input in the cutting zone [50]. Correspondingly, larger amount of material is removed from the electrode and the target surface which promotes the EWR as indicated in Fig.…”
Section: Influence Of Input Variables For Ewrmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason is that Olive oil has the lower value of dielectric strength (26-41 kV) among the other dielectrics used in this study, and thereof, the ionization of the said biodegradable oil becomes easier. This ionization phenomenon generates high discharge heat input in the cutting zone [50]. Correspondingly, larger amount of material is removed from the electrode and the target surface which promotes the EWR as indicated in Fig.…”
Section: Influence Of Input Variables For Ewrmentioning
confidence: 99%
“…Therefore, the low C p generates less discharge heat during the pulse on time and high flash point of the biodegradable Mustard oil indicates the less volatility and flammability of the oil. Both these characteristics (low C p and high flash point of dielectric) contribute in lowering the value of EWR of Al [50]. Figure 5a shows the microscopic image at 0.5 g/100 ml C p in the Mustard oil, where shallow craters are formed on the surface of the machined electrode surface which is the indication of less erosion of material.…”
Section: Influence Of Input Variables For Ewrmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that canola dielectric offered the smallest dimensional overcut. However, combination of sunflower oil and copper electrode proved as second premier case to reduce the overcut was reported [30]. The EDM performance of the hybrid composite (Al-SiC-Ni) was compared to that of three electrode materials (copper, brass, and graphite) and four bio-diesel-based biodielectrics such as Neem biodiesel (NBD), Jatropha biodiesel (JBD), Pongamia biodiesel (PBD), and Polanga biodiesel (POBD).…”
Section: Introductionmentioning
confidence: 99%